Investigating the Influence of Time Variation on Electric Motor Vibration Characteristics - Rinaldi, Rinaldi; Weriono, Weriono; Hendri, Hendri (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
This research aims to analyze vibrations in a 1750 HP Westinghouse electric motor. The electric motors have an important role in the company's operations. Hence, the vibration analysis may crucial to carried out for optimal performance and prevent potential damage. In this research is to find out the vibrations that occur according to the permitted vibration standards and to find out the parts of the machine that have an influence in order to minimize the vibrations that occur. Vibration test was carried out using the vibration analyzer as a measuring instrument and temperature testing. The results of the vibration analysis was obtained the vibration values ??on the Drive-End and Non-Drive End sides were still moderate and suitable for operation. The highest vibration value occurred in the first 10-minute test in the Non-Drive End (NDE) vertical direction with an rms value of 0.083 inch/s.